2010
DOI: 10.1515/jbcpp.2010.21.4.295
|View full text |Cite
|
Sign up to set email alerts
|

Extract of Xylopia aethiopica (Annonaceae) Protects Against Gamma-Radiation-Induced Testicular Damage in Wistar Rats

Abstract: Ionizing radiation is an important environmental risk factor and, a major therapeutic agent for cancer treatment. This study was designed to evaluate the protective effect of extract of Xylopia aethiopica (XA) on γ-radiation-induced testicular damage in rats. Vitamin C (VC) served as the reference antioxidant during the study. The study consists of 4 groups of 11 rats each. Group I received corn oil (vehicle), groups II and IV were pretreated with XA (250 mg/kg) and VC (250mg/kg) for 6 weeks before and 8 weeks… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(22 citation statements)
references
References 27 publications
1
21
0
Order By: Relevance
“…These results are comparable with those of Chen et al (2002). In this context, Adaramoye et al (2010) and El-Marakby et al (2016) verified that exposure to γ-radiation leads to a significant increase in testicular lipid peroxidation associated with a marked decline in testicular CAT. Furthermore, a number of studies have reported that FA could scavenge free radicals, increase reduced glutathione content and constrains lipid peroxidation in vivo and in vitro (Gohil et al, 2012).…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…These results are comparable with those of Chen et al (2002). In this context, Adaramoye et al (2010) and El-Marakby et al (2016) verified that exposure to γ-radiation leads to a significant increase in testicular lipid peroxidation associated with a marked decline in testicular CAT. Furthermore, a number of studies have reported that FA could scavenge free radicals, increase reduced glutathione content and constrains lipid peroxidation in vivo and in vitro (Gohil et al, 2012).…”
Section: Discussionsupporting
confidence: 81%
“…The animals were exposed to a single dose of (5Gy) gamma rays with a dose rate of 0.125Gy/ min. This dose represents the sub-lethal dose for rats according to the study of Adaramoye et al (2010).…”
Section: Gamma-radiationmentioning
confidence: 99%
“…X. aethiopica has been found to contain some phytochemicals, which exhibit a wide range of biological effects as a consequence of their antioxidant properties (78).…”
Section: Berry and Plant Extracts/phytochemicalsmentioning
confidence: 99%
“…In otherwise, obtained results of (LEBH+RT) group confirm that LEBH played an important role in healing tumor and improves radiation effect more than radiation effect alone (39) . Lipid peroxidation has been suggested as one of the molecular mechanisms involved in radiation induced damage (45) . In the present study, the increased level of MDA for control and RT groups an index of lipid peroxidation may be due to the free radicals attack on cell membrane phospholipids and circulating lipids (46) .…”
Section: Discussionmentioning
confidence: 99%